THE PROBLEM OF TRANSLATING NEOLOGISMS FROM FRENCH INTO UZBEK (Academicia Globe: Inderscience Research, 2022)
Today, in the age of technology, neologisms are becoming more common. Neologisms are words that have just entered the language and have been mastered as new words from different languages. It is good for everyone to study neologisms, even if they are for themselves, because these words have come to us from other languages, so we need to know their exact and correct meaning and use them in their place. we need to learn. Uzbek, like other languages, is learning new words from French. This article will give you a brief overview of French neologisms. In addition, brief answers were given to questions such as from which languages new words are entering the French language, from which language they are currently learning more neologisms, and from what situation they were before. The article provides sample explanations of neologisms that have come to us from the French in recent months. In general, through this article we will find answers to questions we do not know about new words in French and strengthen our knowledge of neologisms.